2013
DOI: 10.1002/j.1532-2149.2013.00299.x
|View full text |Cite
|
Sign up to set email alerts
|

After‐effects of cognitive control on pain

Abstract: Background: The higher order processes involved in self-regulation are generally thought to depend on cognitive (attentional/executive) functions with limited resources. Experimental studies further show that exerting self-control in a first task results in decreased performance in other following self-control tasks, which may be interpreted as the consequence of either effective or perceived resource depletion outlasting the first task. Given that higher order cognitive/attentional processes are also consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
54
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(72 citation statements)
references
References 43 publications
14
54
4
Order By: Relevance
“…In accordance with the hypothesis, the results show that VAS scores were lower during Stroop sessions compared to sessions with stimulus-evoked pain without Stroop and with no differences between Stroop-pain and Stroop-pain-conditioning. These results support top-down analgesia possibly derived via cortical and/or subcortical regions (Damien, Colloca, Bellei-Rodriguez, & Marchand, 2018;Wiech, 2016), and align with the existing literature showing that Stroop is sufficient to reduce pain sensitivity in healthy participants (Bantick et al, 2002;Fechir et al, 2009;Martinsen et al, 2014Martinsen et al, , 2018Oosterman et al, 2010;Wilder-Smith et al, 2013) although one study found increased pain with increased cognitive load (Silvestrini & Rainville, 2013) and no significant difference in pain sensitivity was found in another study (Aniskin et al, 2011). Of previous studies only three looked at differences between congruent and incongruent paradigms with regards to pain sensitivity (Bantick et al, 2002;Martinsen et al, 2014Martinsen et al, , 2018 and a difference was only found in one of the three (Bantick et al, 2002).…”
Section: The Effect Of Stroop Task On Pain Intensitysupporting
confidence: 89%
See 1 more Smart Citation
“…In accordance with the hypothesis, the results show that VAS scores were lower during Stroop sessions compared to sessions with stimulus-evoked pain without Stroop and with no differences between Stroop-pain and Stroop-pain-conditioning. These results support top-down analgesia possibly derived via cortical and/or subcortical regions (Damien, Colloca, Bellei-Rodriguez, & Marchand, 2018;Wiech, 2016), and align with the existing literature showing that Stroop is sufficient to reduce pain sensitivity in healthy participants (Bantick et al, 2002;Fechir et al, 2009;Martinsen et al, 2014Martinsen et al, , 2018Oosterman et al, 2010;Wilder-Smith et al, 2013) although one study found increased pain with increased cognitive load (Silvestrini & Rainville, 2013) and no significant difference in pain sensitivity was found in another study (Aniskin et al, 2011). Of previous studies only three looked at differences between congruent and incongruent paradigms with regards to pain sensitivity (Bantick et al, 2002;Martinsen et al, 2014Martinsen et al, , 2018 and a difference was only found in one of the three (Bantick et al, 2002).…”
Section: The Effect Of Stroop Task On Pain Intensitysupporting
confidence: 89%
“…Pain inhibition during distraction and CPM are not the same (Lautenbacher, Prager, & Rollman, 2007;Moont, Crispel, Lev, Pud, & Yarnitsky, 2012;Moont et al, 2010). In support of this, CPM effects do not diminish when repeated over 20 minutes (Hoegh, Petersen, & Graven-Nielsen, 2018) while attention-induced analgesia does (Silvestrini & Rainville, 2013). However, some authors suggest that CPM and attention could depend on the capacity of the same descending control systems (MacLeod, 1992;Silvestrini & Rainville, 2013;Stroop, 1935).…”
Section: Introductionmentioning
confidence: 92%
“…Therefore, there was not a direct pain measurement, nor an objective evidence of the level of the nociceptive sensitization. Silvestrini and Rainville (), beyond showing an increased subjective pain perception after a highly demanding cognitive task, demonstrated that the sensitization to the painful stimuli begins from the nociceptive input processing at the spinal cord level (increased NFR score). This last finding means that the increased pain perception is a top‐down process, beginning with the allocation of cognitive resources (numerical Stroop task) and leading to a reduced efficiency of the descending pain control mechanisms.…”
mentioning
confidence: 99%
“…This is nothing else than what sportsmen define as ‘mental energy recovery’ between two consecutive competitions. Second, in the study by Silvestrini and Raiville's (), the subjects were asked to rate pain due to a train of electrical stimuli. Each train was very short, lasting 30 ms.…”
mentioning
confidence: 99%
See 1 more Smart Citation